Effects of drugs and substance on conduct disorder among the young offenders in Shikusa Borstal Institution, Kenya - Moracha, Edward N.; Mbiriri, Michael; Bironga, Sophia (My University, 2021)
The main aim of the study was to assess the effects of drugs and substance on conduct disorder among the young offenders in Shikusa Borstal Institution. The study adopted a descriptive design. The target population was 248, simple random and census sampling methods were applied to select 92 respondents as the sample size. Primary data was gathered through closed-ended questionnaires. Descriptive and inferential statistical techniques were utilized to analyze quantitative data while verbatim accounts were used for qualitative data. The results were presented using tables and figures. The study established that Proximity of substance and drugs has made easier for young offenders to access them with highest mean of (2.7204), drop out school had the lowest mean of (2.1290). These findings indicated that the ease at which young offenders access drugs and substance has increased the consumption rate among young offenders hence increasing their numbers in Shikusa Borstal institution. The study found out that drug and substance had positive and a significant effect on conduct disorder among young offenders, hence a unit change in Drug and substance resulting to a significant positive change on conduct disorder among young offenders. Further, the study offers suggestive evidence that Substance and drug abuse had a positive but weak correlation with conduct disorder.
Keywords: drugs and substance; conduct disorder; young offenders